Canadian High School Rugby Coaches Readiness for an Injury Prevention Strategy Implementation: Evaluating a Train-the-Coach Workshop - Shill, Isla J.; Räisänen, Anu; Black, Amanda M.; Barden, Craig; van den Berg, Carla; McKay, Carly D.; West, Stephen W.; Pasanen, Kati; Hagel, Brent E.; Emery, Carolyn A. (Frontiers in Sports and Active Living, 2021)
Background: Canadian rugby coach injury prevention beliefs and attitudes have not been studied, yet are key to informing injury prevention strategy implementation. Despite neuromuscular training (NMT) warm-up success in reducing injury, adoption of these programs is variable. Therefore, objectives of this study included (1) describing Canadian youth rugby coach injury prevention beliefs and attitudes and current warm-up practices and (2) evaluating intention to use a rugby-specific NMT warm-up. Methods: High school rugby coaches completed a questionnaire before and after a rugby-specific NMT warm-up workshop. The pre-workshop questionnaire captured demographics, current warm-up practice, and NMT warm-up knowledge and use. Both questionnaires captured injury prevention beliefs, attitudes and behavioral intention. Results: Forty-eight coaches participated in the workshops. Pre-workshop, 27% of coaches were aware of NMT warm-ups. Coaches primarily included aerobic and stretching components, while balance components were not common in their warm-ups over the past year. Additionally, 92% of coaches agreed to some extent they would “complete a rugby-specific warm-up program prior to every game and training session this season.” Post-workshop, 86% of coaches agreed to some extent that they would use the program in every rugby session. No differences were observed between pre- and post-workshop intention to implement the warm-up (p = 0.10). Interpretation: This is the first study to examine current Canadian youth rugby coach warm-up practices and intention to use NMT warm-ups. Canadian rugby coach intention to use a rugby-specific NMT warm-up is high, providing ample opportunity to investigate the efficacy of a NMT warm-up in youth rugby.